A novel probabilistic forecast system predicting anomalously warm 2018-2022 reinforcing the long-term global warming trend - Florian Sévellec (Nature Portfolio, 2018)
Accurate near-term predictions of global temperatures are required to determine some of the key impacts of climate change. Here the authors develop a novel probabilistic forecast system that shows anomalously warm temperatures for the next years with increased risk of extreme warming.